Strategic alliance in technological development and innovation: Performance evaluation of co-creation between companies and their supply chain - Luiz Otavio Monteiro; Jose Rodrigues Faria Filho; Leandro Barreto; Alessandro Correa; Alberto Argolo; Jose Marcio Gramacho (Journal of Industrial Engineering and Management, 2013)
Purpose: The Brazilian oil and gas market presents a perspective of growth in the next decades. Considering this scenario, the increasing number of participants in this supply chain is foreseen to supply the demand of goods and services, especially in the technological development area. The paper intends to evaluate the collaborative development capacity and respective measurements of performance on these partnerships established between customer and suppliers, through qualitative research with a sample of Brazilian oil and gas market representative. Design/methodology/approach: This paper intends to verify if the co-creation performance is measured after an implementation, specific in a restricted industry. The methodology consists in a bibliographical research to support the study, and it also had a questionnaire sent to Brazilian companies that take part of the oil and natural gas industry supply chain, to analyze if the results of co-creation activities are measured by this group of companies, to verify its attractiveness to develop the co-creation usage or change the type of partnership with the market. Findings and Originality/value: The misunderstanding of co-creation and technical partnership was noticed. The usage of teams working together from two or more organizations cannot be considered as a co-creation, because the relationship and obligations are different between these two ways of workgroup. But the companies of oil and gas industry, when questioned, were able to distinguish it, avoiding risks of incorrect results motivated by wrong interpretation of the paper content. Research limitations/implications: As related in the paper, eight companies were invited to take part on the questionnaire about co-creation, but only 50% answered it. The research should have a better result of this subject if it had been developed with more answers of Brazilian oil and gas industry companies. Originality/value: Even this kind of partnership is used in oil and natural gas industrial segment, the measurement isn´t correct used. The value of this paper is to show that companies that are using co-creation could detect the best opportunities to apply it, due to the attractiveness that each situation can generate.